Multimedia presentation, cognitive processes, learning: an experimental research in university teaching - Ganino, Giovanni (Formazione & insegnamento, 2018)
This research project comes from the need to reflect upon formative practices and their models, focusing on the consequences, not always explicit, that they have towards behaviours and learning. The specific aim of this research was to analyse the main epistemological paradigms that guide university professors in their use of cognitive artifacts, paying particular attention to the web conferencing. In order to significantly impact learning processes, each cognitive artifact must be designed and used following precise theoretical paradigms binding its use. Based on existing guidelines regarding multimedia learning from international studies, the didactic functionality of multimedia presentation within the ambito of university teaching was verified. Once a hypothesis was identified, experimental research was carried out with intentional manipulation of independent variables; the result was measured through a dependent variable (learnings). A control group and two experimental groups participated in the study. A methodology and the related tools to be used were prepared. Finally, after having identified the sample, an operative plan was elaborated including times and places, methods of analysis. Therefore, whilst applying a quantitative methodology, the qualitative elements have not been neglected. The analysis undertaken in this study considered not only the relationships between data and information but also the significant connections within the studied phenomenon. It is a system consistent with a hermeneutic epistemological approach, which refers to an interpretative pedagogy. The research results confirmed the hypothesis: learning outcomes increase when the valorisation of the didactic content as presented by the university teacher through web conferencing, is in accordance with the principles relating to multimedia learning.